The headless Cupid - Snyder, Zilpha Keatley; Raible, Alton, 1918- (New York : Dell Yearling, 1971)
Life is never quite the same again for eleven-year-old David after the arrival of his new stepsister, a student of the occult.
Keywords: Family life -- Fiction; Haunted houses -- Fiction; Magic -- Fiction; Stepfamilies -- Fiction